2020
DOI: 10.1186/s12960-020-0452-7
|View full text |Cite
|
Sign up to set email alerts
|

Is enhancing the professionalism of healthcare providers critical to tackling antimicrobial resistance in low- and middle-income countries?

Abstract: Background: Healthcare providers' (HCPs) professionalism refers to their commitment and ability to respond to the health needs of the communities they serve and to act in the best interest of patients. Despite attention to increasing the number of HCPs in low-and middle-income countries (LMIC), the quality of professional education delivered to HCPs and their resulting professionalism has been neglected. The Global Action Plan on Antimicrobial Resistance (AMR) seeks to reduce inappropriate use of antibiotics b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 41 publications
(47 reference statements)
1
21
0
Order By: Relevance
“…Enhance the professionalism of HCWs including initiatives to reduce inappropriate prescribing of antimicrobials where this occurs ( Godman et al., 2020a ; Khan et al., 2020 )…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Enhance the professionalism of HCWs including initiatives to reduce inappropriate prescribing of antimicrobials where this occurs ( Godman et al., 2020a ; Khan et al., 2020 )…”
Section: Resultsmentioning
confidence: 99%
“…• Enhance the professionalism of HCWs including initiatives to reduce inappropriate prescribing of antimicrobials where this occurs (Godman et al, 2020a;Khan et al, 2020 • Promote and fund operational/national research on the impact of COVID-19 on infectious diseases (including AMR) and non-infectious diseases especially the unintended consequences ( Table 3). This is particularly important in Africa where national programmes are just starting to address AMR as well as NCDs including CVD, diabetes, and mental health (Mendelson and Matsoso, 2015;Keates et al, 2017;Ghana Ministry of Health, 2018;Godman et al, 2020a;Godman et al, 2020b;Godman et al, 2020c) • Continue to promote research into potential risk factors for morbidity and mortality among African patients given the differences that can exist between patients in Africa and those in high income countries • Continue with research programmes aimed at mitigating against infectious diseases (including AMR) and non-infectious diseases across countries to add to the debate about the potential impact of unintended consequences • Instigate research into new ways to manage patients with both infectious diseases and NCDs where there are constraints on patient access including better use of new technologies including telemedicine and consultations through the internet/ mobile telephones NB: AMR, Antimicrobial Rsistance; CVD, Coronary Vascular Disease; EBM, Evidence-base medicine; HTA, Health Technology Assessment; NCDs, Noncommunicable diseases; PPE, Personal Protective Equipment; SME, Small and Medium size enterprise.…”
Section: Leadership and Governancementioning
confidence: 99%
“…Pharmacists and others could also offer online or phone counseling services for patients, promote the rational use of medicines, and potentially offer vaccination services 130,135 . However, this may require improved professionalism among pharmacists and store owners [136][137][138] . Pharmacists and others also need to balance demand and supply of medicines, which is essential in countries with high patient copayments and existing concerns with the availability of medicines in healthcare facilities 126,139 .…”
Section: Role Of Pharmacists and Others In Drug Stores In The Preventmentioning
confidence: 99%
“…However, in keeping with ndings in India [41,42], our study also found that attendance by pharmacists does not guarantee appropriate dispensing, partly due to potential con icts of interest between their professional ethics and the economic incentives of those who own and manage the pharmacies. Another reason is that some pharmacists were reluctant to deny antibiotics to clients who asked for them, suggesting that the educational curriculum in universities should be reformed to include speci c training on interpersonal communication skills to manage patient demand for medications [43,44].…”
Section: Discussionmentioning
confidence: 99%